Southern Writers Bear Witness : Interviews - Gretlund, Jan Nordby (Book collections on Project MUSE., 2018)
"Jan Nordby Gretlund has been studying the literature of the American South for some fifty years, and his outsider's perspective as a European scholar has made him an intellectually acute witness of both the literature and its creators. Whether it is their language and reflexive storytelling or the craft and techniques by which writers transform life and experience into art that fascinates Gretlund, elements of their fiction led to his interviews with the fourteen storytellers featured in Southern Writers Bear Witness. Gretlund believes a good interview will always reveal something about a writer's life and character, details that can inform a reading of that writer's fiction. The interviewer's task, according to Gretlund, is to supply the reader with some of the sources and experiences that inspired and shaped the fiction. Through his conversations Gretlund also occasionally elicits the subjects' reflections on other writers and their work to discover affiliations, lines of influence, and divergences, and he also emphasizes the enduring power of their work"--